2015
DOI: 10.1177/0363546515570850
|View full text |Cite
|
Sign up to set email alerts
|

Placement of Double Tunnels in ACL Reconstruction Using Bony Landmarks Versus Existing Footprint Remnant

Abstract: Although both techniques provided satisfactory clinical results, DB-ACLR using the existing footprint remnant for tunnel placement showed better functional results with respect to faster ROM recovery, higher subjective outcome scores, and better arthroscopic second-look with no revision cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 28 publications
0
38
0
4
Order By: Relevance
“…Considering the heterogeneity in anatomic landmarks, placement of the tibial tunnel using an existing footprint remnant might be a better approach than using bony or meniscal landmarks to restore the anatomic position of the ACL. Supporting this, a recent study showed that ACL reconstructions using an existing footprint remnant for tunnel placement provide better objective and subjective clinical results than reconstructions using bony landmarks (Lu et al 2015). …”
Section: Discussionmentioning
confidence: 90%
“…Considering the heterogeneity in anatomic landmarks, placement of the tibial tunnel using an existing footprint remnant might be a better approach than using bony or meniscal landmarks to restore the anatomic position of the ACL. Supporting this, a recent study showed that ACL reconstructions using an existing footprint remnant for tunnel placement provide better objective and subjective clinical results than reconstructions using bony landmarks (Lu et al 2015). …”
Section: Discussionmentioning
confidence: 90%
“…Most studies had retrospective, non-randomized designs. There were only five randomized controlled trials or prospective cohort studies (levels of evidence I and II) [7,8,14,17,18], probably because of the invasive nature of second-look arthroscopy. Eleven of the remaining 23 studies were retrospective comparative studies (level of evidence III) and 12 studies were case series (level of evidence IV).…”
Section: Study Quality Assessmentmentioning
confidence: 99%
“…1). All studies except one [19] were from northeast Asian regions including South Korea [6, 9-11, 14, 20, 22, 24, 26, 27, 31, 33], Japan [5,7,8,12,13,17,21,23,25,[28][29][30]32], and China [18,34]. Year of publication ranged from 1994 to 2017.…”
Section: Study Identification and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soft tissue remnants, along with bony landmarks, are essential in determining the anatomic tunnel positions during ACL reconstruction surgery 67 68. A deficient interobserver agreement between surgeons can be present if these structures are not considered for anatomic tunnel placement 69…”
Section: Acl Reconstruction: Current State Of the Artmentioning
confidence: 99%